Multidimensional evaluation of the clinical efficacy and potential mechanisms of acupuncture combined with rehabilitation training in the treatment of stroke: a study based on multiple evaluation indicators - Xie, Jingjun; Li, Jinxia; Sun, Qi; Jiang, Jie (Frontiers in Neurology, 2025)
ObjectiveThis study aims to explore the therapeutic effects and potential mechanisms of acupuncture combined with rehabilitation training on stroke patients.MethodsA total of 120 stroke patients were randomly divided into a control group (Group A), a rehabilitation training group (Group B), and an acupuncture combined with rehabilitation training group (Group C), with 40 patients in each group. The National Institute of Health Stroke Scale (NIHSS) for neurological deficit, the Barthel Index for activities of daily living ability were evaluated before treatment, 4, 8, and 12 weeks after treatment. Additionally, the levels of serum brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and inflammatory factors (IL-6, TNF-α) were detected.ResultsThe acupuncture combined with rehabilitation training group (Group C) was significantly superior to the other two groups (Group A and Group B) in improving neurological function, activities of daily living ability, and regulating serum factor levels.ConclusionAcupuncture combined with rehabilitation training is an effective treatment regimen for stroke, providing a theoretical and practical basis for clinical application.